A Prospective, Randomized Investigation of Syndesmosis Injury Fixation. Issue 2 (2nd July 2020) - Giza, Eric; Oliver, Todd; Barousse, Patrick S.; Allen, Tyler; Shelton, Trevor; Sarcon, Aida K.; Sathy, Ashoke; Faerber, Wade; Lin, Johnny L.; Stannard, James P.; Crist, Brett; Rocca, Gregory J. Della; et al.
Category: Ankle; Trauma Introduction/Purpose: Syndesmotic disruption occurs in 10 to 13% of all ankle fractures. It is present in 15 cases per 100, 000 of the general population. There has been debate on the best treatment for syndesmotic injuries. The typical surgical treatments include fixation with either screws or suture button devices. The purpose of this study is to compare clinical outcomes of syndesmotic injuries treated surgically with either screws or suture button devices. It was hypothesized that suture button fixation would provide equal clinical results with less need for hardware removal. Methods: This was a multi-center, randomized, prospective clinical trial comparing two surgical interventions for treatment of acute syndesmotic injury. Subjects were placed into either screw fixation or the Suture-button device group. Subjects with clinical signs or radiographic evidence of syndesmotic injury were asked to participate in this study. Inclusion criteria was ages 18 to 65 years old with confirmed syndesmotic instability. The primary outcomes of the study were VAS scores (activity, pain, satisfaction) and FFI scores (pain, disability, activity) which were collected at preoperative state, 6 weeks, and 12 months postoperatively. Results: Sixty-five subjects were enrolled in this study. Thirty-two subjects received Suture-button fixation (49%) and 33 received screw fixation (51%). VAS scores and FFI scores for subjects treated with the Suture-button device or screw fixation comparing preoperative, six-week, and 12-month scores all showed clinical improvement. There was no significant difference between the two treatment groups (p >0.05).Nine subjects (27%) in the syndesmotic screw fixation group experienced adverse events, and only one subject (3%) in the suture-button group had adverse event. Conclusion: The short-term clinical outcomes suggest that both syndesmotic screws and suture-button devices are effective treatment options to address acute syndesmotic injuries. In the short-term (12-months), suture-button fixation resulted in significantly less adverse events compared to syndesmotic screw fixation group.